Impact of Mining Activities Against Sand Stone Sustainability Agricultural Resources and Power Lenek In the village of Desa Lenek Kali Bambang District of Aikmel - Nurul - In; I Putu Sriartha; Putu Ananda Citra (Universitas Pendidikan Ganesha, 2016)
This research was conducted in the village of Lenek Daya and Kali Bambang, District of Aikmel, East Lombok. This study aims to: (1) to describe the characteristics of sand mining activities rocks in the village of Lenek Daya and Kali Bambang District of Aikmel, (2) Describe the process of the development of the management of sand mining activities rocks in the village of Lenek Daya and Kali Bambang District of Aikmel, ( 3) to analyze the impact of sand mining activities stones on the sustainability of agricultural resources in the village Lenek Daya and Kali Bambang District of Aikmel. This research is a analysis descriptive quantitative and qualitative. These samples included 71 people taken by